Solid electrolytic capacitor and method for manufacturing solid electrolytic capacitor
The solid electrolytic capacitor with a dual electrolyte layer structure and fixed electrolyte layers addresses the need for higher capacitance density in miniaturized capacitors, ensuring effective performance and reliability.
Patent Information
- Application Number
- JP2023106818
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-29
- Publication Date
- 2025-01-17
AI Technical Summary
There is a demand for smaller solid electrolytic capacitors with improved capacitance appearance rate per unit volume to meet the needs of miniaturized electronic devices.
A solid electrolytic capacitor design featuring a dielectric layer, an ion-conducting first electrolyte layer, and an electron-conducting second electrolyte layer, with the first electrolyte layer containing a specific material represented by formula (1), and a manufacturing process involving silane coupling agents to fix the electrolyte layers on the dielectric layer, enhancing ion and electron conductivity.
The design improves the capacitance appearance rate and prevents leakage of ionic liquids, maintaining capacitor performance and reducing defects.
Smart Images

Figure 2025006181000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a solid electrolytic capacitor and a method for manufacturing a solid electrolytic capacitor. [Background technology]
[0002] In recent years, solid electrolytic capacitors have come to be widely used in various fields such as electronic devices, etc. Patent Document 1 discloses a technique relating to a solid electrolytic capacitor that uses a conductive polymer as the solid electrolyte. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-69082 Summary of the Invention [Problem to be solved by the invention]
[0004] As described above, solid electrolytic capacitors are widely used in various fields such as electronic devices. In recent years, the miniaturization of electronic devices has led to a demand for miniaturization of solid electrolytic capacitors. For this reason, it is necessary to miniaturize solid electrolytic capacitors while maintaining their capacitance, and it is necessary to improve the capacitance occurrence rate per unit volume of solid electrolytic capacitors.
[0005] In view of the above problems, an object of the present disclosure is to provide a solid electrolytic capacitor capable of improving the capacitance appearance rate of the solid electrolytic capacitor, and a method for manufacturing the solid electrolytic capacitor. [Means for solving the problem]
[0006] A solid electrolytic capacitor according to an embodiment of the present disclosure includes an anode body made of a valve metal, a dielectric layer formed on the anode body, and a solid electrolyte layer formed on the dielectric layer, the solid electrolyte layer having a first electrolyte layer formed on the dielectric layer and a second electrolyte layer formed on the first electrolyte layer, the first electrolyte layer being an ion-conducting electrolyte layer, and the second electrolyte layer being an electron-conducting electrolyte layer.
[0007] A method for manufacturing a solid electrolytic capacitor according to one embodiment of the present disclosure includes a first step of forming a dielectric layer on an anode body made of a valve metal, and a second step of forming a solid electrolyte layer on the dielectric layer. The second step includes a third step of forming a first electrolyte layer on the dielectric layer, and a fourth step of forming a second electrolyte layer on the first electrolyte layer, and the third step includes a step of forming a layer containing a material represented by the following formula (1) on the dielectric layer: [ka] In the above formula (1), M represents a valve metal atom. R 1+ represents at least one cationic functional group selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, phosphonium derivatives, and sulfonium derivatives, and may have a carbon chain having 1 to 20 carbon atoms between the cationic functional group and the Si molecule, and the carbon chain may have an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or a heterocycle between the chains. In the above formula (1), R 2 represents any one of a hydrogen atom, a carbon chain having 1 to 4 carbon atoms, a valve metal atom, or a polymer in which units of formula (1) are condensed and polymerized together and linked by -Si-O-Si-. In the above formula (1), X -are chlorine, bromine, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methylsulfuric acid, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropanoic acid, thiosalicylic acid, thiocyanic acid, dicyanamide, dimethyl It represents at least one anion selected from phosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroferrate(III), tris(trifluoromethylsulfonyl)methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide. Effect of the Invention
[0008] The present disclosure makes it possible to provide a solid electrolytic capacitor capable of improving the capacitance appearance rate of the solid electrolytic capacitor, and a method for manufacturing the solid electrolytic capacitor. [Brief description of the drawings]
[0009] [Figure 1] 1 is a cross-sectional view of a solid electrolytic capacitor according to an embodiment. [Diagram 2] 2 is a cross-sectional view showing an example of a solid electrolyte layer included in the solid electrolytic capacitor according to the embodiment; FIG. [Diagram 3] 4 is a flowchart illustrating a method for manufacturing a solid electrolytic capacitor according to an embodiment. [Figure 4] FIG. 2 is a schematic diagram for illustrating a method for producing a first electrolyte layer (production method A). [Diagram 5] FIG. 4 is a schematic diagram for illustrating a manufacturing method (manufacturing method B) of the first electrolyte layer. [Figure 6]FIG. 4 is a schematic diagram for illustrating a method for producing a first electrolyte layer (production method C). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] <Solid electrolytic capacitor> Hereinafter, an embodiment will be described with reference to the drawings. Fig. 1 is a cross-sectional view of a solid electrolytic capacitor according to an embodiment. As shown in Fig. 1, solid electrolytic capacitor 1 according to the present embodiment includes anode body 11, dielectric layer 12, solid electrolyte layer 13, cathode layer 16, conductive adhesive 17, anode lead 18, exterior resin 19, and lead frames 20a and 20b.
[0011] The anode body 11 is made of a porous valve metal. For example, at least one selected from tantalum (Ta), aluminum (Al), niobium (Nb), titanium (Ti), zirconium (Zr), hafnium (Hf), and tungsten (W), or an alloy of these metals, can be used for the anode body 11. In particular, it is preferable that the anode body 11 is made of at least one selected from tantalum (Ta), aluminum (Al), and niobium (Nb), or an alloy of these metals. The anode body 11 is formed, for example, by using a plate-shaped, foil-shaped, or linear valve metal, a sintered body containing fine particles of the valve metal, or a porous valve metal that has been subjected to a surface enlargement treatment by etching.
[0012] Dielectric layer 12 is formed on the surface of anode body 11. For example, dielectric layer 12 can be formed by anodizing the surface of anode body 11. For example, the surface of anode body 11 is porous, and dielectric layer 12 is also formed in the pores of this porous material. For example, when tantalum is used for anode body 11, a tantalum oxide coating (dielectric layer 12) can be formed on the surface of anode body 11 by anodizing anode body 11. For example, the thickness of dielectric layer 12 can be appropriately adjusted by the voltage of anodization.
[0013] The solid electrolyte layer 13 is formed on the dielectric layer 12. The solid electrolyte layer 13 is formed so as to be in contact with the entire surface of the dielectric layer 12. The details of the solid electrolyte layer 13 will be described later.
[0014] The cathode layer 16 is formed on the solid electrolyte layer 13. The cathode layer 16 can be formed, for example, by laminating a carbon layer and a silver layer. Note that the carbon layer and the silver layer are only examples, and the material constituting the cathode layer 16 is not particularly limited as long as it is a material that exhibits electrical conductivity.
[0015] As described above, in the solid electrolytic capacitor 1 according to the present embodiment, the dielectric layer 12, the solid electrolyte layer 13, and the cathode layer 16 are laminated in this order on the anode body 11. The anode body 11 is provided with an anode lead 18, which is connected to the lead frame 20a. For example, the anode lead 18 is connected to the lead frame 20a by welding. The cathode layer 16 is connected to the lead frame 20b via a conductive adhesive 17. The solid electrolytic capacitor 1 according to the present embodiment is covered with an exterior resin 19 with parts of the two lead frames 20a, 20b exposed to the outside.
[0016] <Structure of solid electrolyte layer> Next, a detailed description will be given of solid electrolyte layer 13 included in solid electrolytic capacitor 1 according to the present embodiment. Fig. 2 is a cross-sectional view showing an example of a solid electrolyte layer included in a solid electrolytic capacitor according to the present embodiment, and is an enlarged cross-sectional view of the vicinity of dielectric layer 12 and solid electrolyte layer 13 of solid electrolytic capacitor 1 shown in Fig. 1.
[0017] 2, the solid electrolyte layer 13 includes a first electrolyte layer 21 and a second electrolyte layer 22. The first electrolyte layer 21 is formed on the dielectric layer 12. The first electrolyte layer 21 is an ion-conducting electrolyte layer, and the second electrolyte layer 22 is an electron-conducting electrolyte layer.
[0018] In the present embodiment, the first electrolyte layer 21 includes, for example, a material represented by the following formula (1). [ka]
[0019] In the above formula (1), M represents a valve metal atom. That is, M is a valve metal atom constituting anode body 11, specifically, a valve metal atom contained in dielectric layer 12. For example, when anode body 11 is made of tantalum (Ta), dielectric layer 12 is tantalum oxide (Ta2O5), and M is a tantalum atom.
[0020] In the above formula (1), R 1+ represents at least one cationic functional group selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, phosphonium derivatives, and sulfonium derivatives, and may have a carbon chain having 1 to 20 carbon atoms between the cationic functional group and the Si molecule, and the carbon chain may have an ester bond, ether bond, amide bond, imide bond, carbon-carbon unsaturated bond, carbon ring, or heterocycle between the chain.
[0021] In the above formula (1), R 2 represents a hydrogen atom, a carbon chain having 1 to 4 carbon atoms, a valve metal atom, or a polymer formed by condensation polymerization of the formula (1) and linking the two with -Si-O-Si-. Here, the polymer formed by linking the two with "-Si-O-Si-" is the "-OR 2 " are polymerized with each other, and adjacent formula (1)s are linked by "-Si-O-Si-".
[0022] In the above formula (1), X -are chlorine, bromine, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methylsulfuric acid, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropanoic acid, thiosalicylic acid, thiocyanic acid, dicyanamide, dimethyl It represents at least one anion selected from phosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroferrate(III), tris(trifluoromethylsulfonyl)methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide.
[0023] In the first electrolyte layer 21, M in the above formula (1) is a valve metal atom present on the surface of the dielectric layer 12, and the first electrolyte layer 21 is covalently bonded to the surface of the dielectric layer 12 as shown by Si-OM (see Figures 4 to 6), and further, the first electrolyte layer 21 is in contact with the second electrolyte layer 22.
[0024] In the present embodiment, the electrical conductivity of the second electrolyte layer 22 is preferably higher than the electrical conductivity of the first electrolyte layer 21.
[0025] The second electrolyte layer 22 is an electron-conducting electrolyte layer, and is made of, for example, a conductive polymer. For the second electrolyte layer 22, for example, at least one conductive polymer selected from the group consisting of polyethylenedioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof can be used. The second electrolyte layer 22 can be formed by chemical polymerization, electrolytic polymerization, or a method using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer.
[0026] In this embodiment, a third electrolyte layer (not shown) may be further formed on the second electrolyte layer 22. The third electrolyte layer may be formed, for example, using a conductive polymer. For the third electrolyte layer, for example, at least one conductive polymer selected from the group consisting of polyethylenedioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof may be used. The third electrolyte layer may be formed by chemical polymerization, electrolytic polymerization, or a method using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer. When forming the third electrolyte layer, it is preferable to form it by a method different from the method used to form the second electrolyte layer 22.
[0027] <Solid electrolytic capacitor manufacturing method> Next, a method for manufacturing the solid electrolytic capacitor according to the present embodiment will be described. Fig. 3 is a flow chart for explaining the method for manufacturing the solid electrolytic capacitor according to the present embodiment. The method for manufacturing the solid electrolytic capacitor will be described below with reference to Figs. 1 and 2.
[0028] When manufacturing the solid electrolytic capacitor according to this embodiment, first, anode body 11 is formed (step S1). A valve metal can be used for anode body 11. The above-mentioned materials can be used as the valve metal.
[0029] Next, the anode body (valve metal) 11 is anodized to form a dielectric layer 12 on the surface of the anode body 11 (step S2). After that, a first electrolyte layer 21 is formed on the dielectric layer 12 (step S3). The material represented by the above formula (1) can be used for the first electrolyte layer 21. The method for forming the first electrolyte layer 21 will be described in detail later.
[0030] Next, the second electrolyte layer 22 is formed on the first electrolyte layer 21 (step S4). The second electrolyte layer 22 can be formed using, for example, a conductive polymer. For example, the second electrolyte layer 22 can be formed using at least one conductive polymer selected from the group consisting of polyethylenedioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof. The second electrolyte layer 22 can be formed using chemical polymerization, electrolytic polymerization, or a method using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer.
[0031] After forming the second electrolyte layer 22, the cathode layer 16 is formed (step S5). The cathode layer 16 can be formed, for example, by laminating a carbon layer and a silver layer.
[0032] Next, lead frames (electrodes) 20a, 20b are formed (step S6). Specifically, the lead frame 20a is connected to the anode lead 18 by welding. Also, the lead frame 20b is connected to the cathode layer 16 by using a conductive adhesive 17.
[0033] Thereafter, the exterior resin 19 is formed (step S7). At this time, the exterior resin 19 is formed so that a part of the two lead frames 20a, 20b is exposed to the outside. There are no particular limitations on the resin used for the exterior resin 19, but a thermosetting epoxy resin or a method of curing a liquid resin can be used.
[0034] By using the method for manufacturing a solid electrolytic capacitor described above, the solid electrolytic capacitor according to this embodiment can be manufactured.
[0035] <Method of Manufacturing First Electrolyte Layer 21> Next, a description will be given of a method for manufacturing the first electrolyte layer 21. Three manufacturing methods A to C will be described below as the method for manufacturing the first electrolyte layer 21.
[0036] (Manufacturing method A) First, a method A for producing the first electrolyte layer 21 will be described. In the method A, first, an alkoxyl group OR of an ionic liquid (hereinafter, also referred to as RTIL (Room Temperature Ionic Liquid)) represented by the following formula (2) is added to the electrolyte. 3 is hydrolyzed to the following formula (3) having a silanol group. Then, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the following formula (3) are dehydrated and condensed to fix the material of the above formula (1) to the surface of the dielectric layer 12. However, in the following formula (2), R 3 represents a carbon chain having 1 to 4 carbon atoms. Hereinafter, a specific description will be given with reference to a schematic diagram. [ka]
[0037] FIG. 4 is a schematic diagram for explaining a method for producing a first electrolyte layer (production method A). As shown in FIG. 4, in production method A, a first electrolyte layer 21 is formed using an RTIL material 30 having a silane coupling agent portion 31 and a salt portion 32 consisting of an anion and a cation. The salt portion 32 has a cationic functional group 33 and an anion 34. The cationic functional group 33 is represented by "R 1+ " and the anion 34 corresponds to "X - " is supported.
[0038] In the manufacturing method A, the first electrolyte layer 21 is formed using an RTIL material 30 in which a silane coupling agent portion 31 and a salt portion 32 are integrated. Specifically, as shown in the lower diagram of FIG. 4, a silane coupling reaction is caused between the silane coupling agent portion 31 of the RTIL material 30 and an OH group present on the surface of the dielectric layer 12, and the silane coupling agent portion 31 is fixed to the surface of the dielectric layer 12. This allows the salt portion 32 to be fixed to the surface of the dielectric layer 12 using the silane coupling agent portion 31. In the configuration shown in the lower diagram of FIG. 4, anions and cations are electrostatically bonded in the salt portion 32, and the anions can move along the positive charge (i.e., in the left-right direction of the diagram).
[0039] (Manufacturing method B) Next, a manufacturing method B for the first electrolyte layer 21 will be described. In manufacturing method B, first, the alkoxyl group of the amino-silane coupling agent is hydrolyzed to obtain an amino-silane coupling agent having a silanol group. Then, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the amino-silane coupling agent are dehydrated and condensed to fix the amino-silane coupling agent on the surface of the dielectric layer 12 by a covalent bond. Then, the anion X - By contacting the compound with an acid and / or a salt containing - The material is bonded to the above-mentioned compound (1) through electrical interaction. A specific description will be given below with reference to a schematic diagram.
[0040] FIG. 5 is a schematic diagram for explaining a manufacturing method (manufacturing method B) of the first electrolyte layer. As shown in FIG. 5, in manufacturing method B, first, an amino-silane coupling agent is prepared. Then, the alkoxyl group of the amino-silane coupling agent is hydrolyzed to obtain an amino-silane coupling agent having a silanol group. Thereafter, as shown in the upper diagram of FIG. 5, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the amino-silane coupling agent are dehydrated and condensed to fix the amino-silane coupling agent 40 on the surface of the dielectric layer 12 by a covalent bond.
[0041] Then, as shown in the center of Figure 5, an amino-silane coupling agent 40 and phosphoric acid 41 (H2PO4 -) to form a salt. Next, as shown in the lower diagram of FIG. 5, phosphoric acid 41 and RTIL anion 42 are ion-exchanged. Residues (phosphoric acid, etc.) at this time are washed away by alcohol washing. This allows the RTIL anion 42 to be fixed to the surface of the dielectric layer 12. In the configuration shown in the lower diagram of FIG. 5, the amino-silane coupling agent 40 and the RTIL anion 42 are electrostatically bonded, and the RTIL anion 42 can move along the positive charge (i.e., in the left-right direction of the drawing). The RTIL anion 42 that performs ion exchange with phosphoric acid 41 may be any anion that can become an RTIL. The amino-silane coupling agent 40 and phosphoric acid 41 (H2PO4 - When the ion exchange is carried out by contacting the cation with a salt of the RTIL, a solution of a salt containing an anion that can become an RTIL (e.g., a salt that is solid at room temperature and has a cation of Li, K, or Na ion) may be used.
[0042] (Manufacturing method C) Next, a manufacturing method C of the first electrolyte layer 21 will be described. In the manufacturing method C, first, an alkoxyl group of at least one silane coupling agent selected from an amino-based silane coupling agent, an epoxy-based silane coupling agent, and a thiol-based silane coupling agent is hydrolyzed to obtain a silane coupling agent having a silanol group. Then, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the silane coupling agent are dehydrated and condensed to fix the silane coupling agent on the surface of the dielectric layer 12 by a covalent bond.
[0043] Then, an RTIL having an epoxy group represented by the following formula (4) is brought into contact with the silane coupling agent fixed on the surface of the dielectric layer 12 and then heated to bond the epoxy group of the following formula (4) with the amino group, epoxy group, or thiol group of the silane coupling agent to form the material represented by the above formula (1). A specific description will be given below using a schematic diagram. [ka]
[0044] 6 is a schematic diagram for explaining a manufacturing method (manufacturing method C) of the first electrolyte layer. As shown in the upper diagram of FIG. 6, manufacturing method C uses a material 50 having a silane coupling agent moiety 51 and an organic reactive moiety 52. Here, the organic reactive moiety 52 is an amino group, an epoxy group, or a thiol group. In manufacturing method C, the silane coupling agent moiety 51 of the material 50 and an OH group present on the surface of the dielectric layer 12 are subjected to a silane coupling reaction (dehydration condensation) to fix the silane coupling agent moiety 51 to the surface of the dielectric layer 12.
[0045] Thereafter, as shown in the lower diagram of Fig. 6, RTIL 53 having epoxy groups 54 is brought into contact with silane coupling agent 50 fixed on the surface of dielectric layer 12 and then heated to bond epoxy groups 54 with organic reactive sites 52 of the silane coupling agent. This allows RTIL 53 to be fixed on the surface of dielectric layer 12. In the configuration shown in the lower diagram of Fig. 6, anions and cations are electrostatically bonded, and anions can move along the positive charges (i.e., in the left-right direction of the diagram).
[0046] The first electrolyte layer 21 can be formed on the surface of the dielectric layer 12 by using the manufacturing methods A to C described above.
[0047] In this embodiment, a third electrolyte layer may be further formed on the second electrolyte layer 22 as described above. The third electrolyte layer may be formed, for example, using a conductive polymer. For the third electrolyte layer, for example, at least one conductive polymer selected from the group consisting of polyethylenedioxythiophene (PEDOT), polypyrrole, polythiophene, polyaniline, and derivatives thereof may be used. The third electrolyte layer may be formed by chemical polymerization, electrolytic polymerization, or a method using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer. When forming the third electrolyte layer, it is preferable to form it by a method different from the method used to form the second electrolyte layer 22.
[0048] As described above, the solid electrolytic capacitor according to the present embodiment includes the first electrolyte layer 21 and the second electrolyte layer 22 as the solid electrolyte layer 13. The first electrolyte layer 21 is an ionically conductive electrolyte layer, and the second electrolyte layer 22 is an electronically conductive electrolyte layer. In other words, the ionically conductive first electrolyte layer 21 is densely formed on the dielectric layer 12, and the electronically conductive second electrolyte layer 22 exhibiting good conductive properties is formed thereon, so that the capacitance appearance rate of the solid electrolytic capacitor can be improved.
[0049] As described above, in this embodiment, the first electrolyte layer 21 including the salt moiety composed of an anion and a cation derived from the RTIL is fixed to the surface of the dielectric layer 12. This makes it possible to prevent the RTIL from flowing out of the solid electrolyte layer 13, thereby suppressing deterioration of characteristics caused by the outflow of the RTIL.
[0050] That is, when an ionic liquid is used as the solid electrolyte, there is a risk that the ionic liquid may flow out from the solid electrolyte layer 13. For example, when the ionic liquid flows out from the solid electrolyte layer 13 onto the lead frame, the flowed-out ionic liquid may cause the characteristics of the solid electrolytic capacitor to deteriorate (such as an increase in leakage current (LC)). In response to this, in the present embodiment, the first electrolyte layer 21 containing the ionic liquid is fixed to the surface of the dielectric layer 12 using a silane coupling agent or the like. This makes it possible to prevent the ionic liquid from flowing out of the solid electrolyte layer 13, thereby making it possible to prevent deterioration of characteristics caused by the outflow of the ionic liquid. EXAMPLES
[0051] The present disclosure will be described more specifically below based on examples, but the present disclosure is not limited to these examples.
[0052] <Example 1> As a sample according to Example 1, a sample in which the first electrolyte layer 21 was formed using the above-mentioned manufacturing method A (see FIG. 4) was produced.
[0053] Specifically, first, a sintered compact of fine tantalum powder as a valve metal was anodized at 50 V in an aqueous phosphoric acid solution to form a dielectric layer 12 made of tantalum oxide on the entire surface of the sintered compact of fine tantalum powder, thereby forming a capacitor element.
[0054] Next, the first electrolyte layer 21 was formed on the dielectric layer 12 by using the above-mentioned manufacturing method A (see FIG. 4). In Example 1, a methoxysilyl group-introduced alkylamine-TFSI was used as the RTIL material 30 in which the silane coupling agent portion 31 and the salt portion 32 are integrated.
[0055] Next, a second electrolyte layer 22 was formed by chemical polymerization. Specifically, an oxidant was reacted with 3,4-ethylenedioxythiophene, a monomer for forming a conductive polymer, on the first electrolyte layer 21. After that, the unreacted oxidant and monomer were washed away with water or alcohol. This process was repeated several times to form a conductive polymer layer (second electrolyte layer) on the first electrolyte layer 21.
[0056] After the second electrolyte layer 22 was formed, the pellet was immersed in carbon paste, pulled up, and dried at 120°C for 1 hour to form a carbon layer. After the carbon layer was formed, the pellet was immersed in silver paste, pulled up, and dried at 120°C for 1 hour to form a silver layer. Next, the valve metal lead and the electrode were welded and connected. In addition, the silver layer and the electrode were connected using a conductive adhesive. Then, an exterior resin was formed to produce a solid electrolytic capacitor.
[0057] <Examples 2 to 5> As the samples according to Examples 2 to 5, samples in which the first electrolyte layer 21 was formed using the above-mentioned manufacturing method B (see FIG. 5) were produced. Note that, except that the first electrolyte layer 21 was formed using the manufacturing method B, the samples were the same as Example 1.
[0058] In Example 2, KBM-903 (amino-based, hydrophilic, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as the amino-based silane coupling agent 40 shown in FIG. 5. Then, the alkoxyl group of the amino-based silane coupling agent was hydrolyzed to obtain an amino-based silane coupling agent having a silanol group. After that, the OH group bonded to the surface of the dielectric layer 12 and the silanol group of the amino-based silane coupling agent were dehydrated and condensed to fix the amino-based silane coupling agent 40 on the surface of the dielectric layer 12 by covalent bonding.
[0059] Then, as shown in the center of Figure 5, an amino-silane coupling agent 40 and phosphoric acid 41 (H2PO4 - ) to form a salt. Next, as shown in the lower diagram of FIG. 5, 1-ethyl-3-methylimidazolium-bis(trifluoromethylsulfonyl)imide (EMI-TFSI), which is an RTIL, was contacted to ion-exchange phosphoric acid 41 with RTIL anion 42. The RTIL anion 42 at this time was bis(trifluoromethylsulfonyl)imide (TFSI). Residues (phosphoric acid, etc.) were washed away by alcohol washing. In this manner, a first electrolyte layer 21 was formed. The subsequent manufacturing method was the same as in Example 1.
[0060] In Example 3, KBM-573 (amino-based, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino-based silane coupling agent 40. In Example 4, KBM-603 (amino-based, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino-based silane coupling agent 40, and 1-ethyl-3-methylimidazolium-ethylsulfonate (EMI-ES) was used as the RTIL. The RTIL anion 42 at this time was ethylsulfonate (ES). In Example 5, KBM-6803 (amino-based, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the amino-based silane coupling agent 40, and 1-butyl-3-methylpyridinium-bis(fluorosulfonyl)imide (BMP-FSI) was used as the RTIL. The RTIL anion 42 at this time was bis(fluorosulfonyl)imide (FSI). Other than this, the samples according to Examples 3 to 5 were prepared using the same method as in Example 2.
[0061] <Examples 6 to 10> As the samples according to Examples 6 to 10, samples in which the first electrolyte layer 21 was formed using the above-mentioned manufacturing method C (see FIG. 6) were produced. Note that, except that the first electrolyte layer 21 was formed using the manufacturing method C, the samples were the same as Example 1.
[0062] In Example 6, KBM-403 (glycidyl-based, manufactured by Shin-Etsu Chemical Co., Ltd.) was prepared as the material 50 having the silane coupling agent portion 51 and the organic reaction portion 52 shown in FIG. 6. KBM-403 has an epoxy group as the organic reaction portion 52. In Example 6, the silane coupling agent portion 51 of KBM-403 and the OH group present on the surface of the dielectric layer 12 were subjected to a silane coupling reaction (dehydration condensation) to fix the silane coupling agent portion 51 to the surface of the dielectric layer 12.
[0063] Thereafter, as shown in the lower diagram of Fig. 6, an ionic liquid 53 having an epoxy group 54 (epoxy group-introduced alkylamine - TFSI) was brought into contact with the KBM-403 fixed on the surface of the dielectric layer 12 and then heated to bond the epoxy group 54 with the organic reactive site 52 (epoxy group) of the silane coupling agent. In this manner, a first electrolyte layer 21 was formed. The subsequent manufacturing method was the same as in Example 1.
[0064] In Example 7, KBM-903 (amino-based, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the material 50. In Example 8, KBM-573 (amino-based, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the material 50. In Example 9, KBM-603 (amino-based, hydrophilic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the material 50. In Example 10, KBM-6803 (amino-based, hydrophobic type, manufactured by Shin-Etsu Chemical Co., Ltd.) was used as the material 50. Other than this, the samples according to Examples 7 to 10 were produced using the same method as in Example 6.
[0065] <Comparative Example 1> As a sample according to Comparative Example 1, a sample was prepared in which a first electrolyte layer was formed using KBM-403 (glycidyl-based, manufactured by Shin-Etsu Chemical Co., Ltd.). Specifically, the silane coupling agent moiety of KBM-403 and the OH group present on the surface of the dielectric layer were subjected to a silane coupling reaction (dehydration condensation) to fix the silane coupling agent moiety to the surface of the dielectric layer, thereby forming a silane coupling agent layer. The rest of the manufacturing method was the same as that of Example 1.
[0066] <Comparative Example 2> As a sample according to Comparative Example 2, a sample was prepared in which a first electrolyte layer was formed using KBM-403 (glycidyl-based, manufactured by Shin-Etsu Chemical Co., Ltd.). Specifically, the silane coupling agent moiety of KBM-403 and the OH group present on the surface of the dielectric layer were subjected to a silane coupling reaction (dehydration condensation) to fix the silane coupling agent moiety to the surface of the dielectric layer. Then, the KBM-403 fixed on the surface of the dielectric layer 12 was brought into contact with EMI-TFSI to form the first electrolyte layer 21. The subsequent manufacturing method was the same as that of Example 1.
[0067] <Comparative Example 3> As a sample according to Comparative Example 3, a sample was prepared using KBM-403 and EMI-TFSI. Specifically, the silane coupling agent moiety of KBM-403 and the OH group present on the surface of the dielectric layer were subjected to a silane coupling reaction (dehydration condensation) to fix the silane coupling agent moiety to the surface of the dielectric layer, forming a silane coupling agent layer. Next, the oxidizing agent was reacted with the monomer 3,4-ethylenedioxythiophene for forming a conductive polymer. After that, the unreacted oxidizing agent and the monomer were washed with water or alcohol. This was repeated several times to form a conductive polymer layer on the first electrolyte layer 21. Then, this capacitor element was immersed in 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMI-TFSI) which is an ionic liquid for 10 minutes, held at room temperature for 30 minutes, and washed with alcohol. Through this process, an electrolyte layer consisting of a conductive polymer layer and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide which is an ionic liquid was formed. The subsequent manufacturing method is the same as in the first embodiment.
[0068] <Sample evaluation> The solid electrolytic capacitor prepared as described above was mounted on an evaluation board by a reflow soldering process, and then the capacitor characteristics (capacitance appearance rate (Cap appearance rate), characteristic failure rate) were evaluated. The Cap appearance rate was evaluated by calculating the capacitance C0 measured in a 40% sulfuric acid solution after forming a dielectric oxide film by electrolytic oxidation, and the capacitance C1 measured after mounting the electrolytic capacitor on an evaluation board. That is, the Cap appearance rate (%) was calculated using the following formula. Cap appearance rate (%)=C1 / C0×100
[0069] The evaluation of the rate of occurrence of characteristic defects was carried out by mounting electrolytic capacitors on an evaluation board and applying voltage for 500 hours under conditions of 85°C and 85% RH, and calculating from the number of evaluations (20p) and the number of products that experienced characteristic defects among those evaluations.
[0070] The evaluation results of each sample are shown in Table 1. As shown in Table 1, the Cap occurrence rate was 83% or more in Examples 1 to 10, which was a good result. Furthermore, the characteristic defect occurrence rate was 0% in Examples 1 to 10, which was also a good result.
[0071] On the other hand, the Cap appearance rate was a low value of 80% in Comparative Example 1. The reason for this is believed to be that in Comparative Example 1, the first electrolyte layer did not contain an ionic liquid.
[0072] In Comparative Example 2, the Cap appearance rate was 80%, a low value similar to that of Comparative Example 1. The reason for this is believed to be that in Comparative Example 2, the ionic liquid was not fixed to the dielectric layer, so it flowed out during subsequent washing, and no ionic liquid was contained in the first electrolyte layer.
[0073] In Comparative Example 3, the Cap appearance rate was 93% or more, which was a good result. However, the characteristic failure rate in Comparative Example 3 was 10%, which was a high value. The reason for this is thought to be that in Comparative Example 3, the silane coupling agent KBM-403 and the RTIL EMI-TFSI were not electrostatically or chemically bonded, so that the RTIL flowed out of the first electrolyte layer during evaluation.
[0074] [Table 1]
[0075] While the present invention has been described above in accordance with the above-described embodiment, the present invention is not limited to the configuration of the above-described embodiment, and naturally includes various modifications, alterations, and combinations that may be made by a person skilled in the art within the scope of the invention as defined in the claims of the present application. [Explanation of symbols]
[0076] 1. Solid electrolytic capacitor 11 Anode body 12 Dielectric layer 13 Solid electrolyte layer 16 Cathode layer 17 Conductive adhesive 18 Anode lead 19 Exterior resin 20a, 20b Lead frame 21 First electrolyte layer 22 Second electrolyte layer 30 materials 31 Silane coupling agent site 32 Salt Site 33 Cationic Functional Groups 34 Anions 40 Amino silane coupling agents 41 Phosphate 42 RTIL anions 50 materials 51 Silane coupling agent site 52 Organic Reactive Sites 53 Ionic Liquids 54 Epoxy group
Claims
1. an anode body made of a valve metal; a dielectric layer formed on the anode body; a solid electrolyte layer formed on the dielectric layer, The solid electrolyte layer is a first electrolyte layer formed on the dielectric layer; a second electrolyte layer formed on the first electrolyte layer; The first electrolyte layer is an ionically conductive electrolyte layer, and the second electrolyte layer is an electronically conductive electrolyte layer. Solid electrolytic capacitor.
2. The solid electrolytic capacitor according to claim 1 , wherein the first electrolyte layer contains a material represented by the following formula (1): 【Chemistry 1】 In the above formula (1), M represents a valve metal atom. R 1+ represents at least one cationic functional group selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, phosphonium derivatives, and sulfonium derivatives, and may have a carbon chain having 1 to 20 carbon atoms between the cationic functional group and the Si molecule, and the carbon chain may have an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or a heterocycle between the chains. In the above formula (1), R 2 represents a hydrogen atom, a carbon chain having 1 to 4 carbon atoms, a valve metal atom, or a polymer in which units of formula (1) are condensed and polymerized together and linked by --Si--O--Si--. In the above formula (1), X - are chlorine, bromine, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methylsulfuric acid, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropanoic acid, thiosalicylic acid, thiocyanic acid, dicyanamide, dimethyl It represents at least one anion selected from phosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroferrate(III), tris(trifluoromethylsulfonyl)methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide.
3. 3. The solid electrolytic capacitor according to claim 1, wherein in the first electrolyte layer, M in the above formula (1) is a valve metal atom present on the surface of the dielectric layer, the first electrolyte layer is covalently bonded to the surface of the dielectric layer as represented by Si-O-M, and the first electrolyte layer is in contact with the second electrolyte layer.
4. The solid electrolytic capacitor according to claim 3 , wherein the second electrolyte layer has a higher electrical conductivity than the first electrolyte layer.
5. The solid electrolytic capacitor according to claim 1 , wherein the second electrolyte layer comprises a conductive polymer.
6. A first step of forming a dielectric layer on an anode body made of a valve metal; a second step of forming a solid electrolyte layer on the dielectric layer, The second step comprises: a third step of forming a first electrolyte layer on the dielectric layer; and a fourth step of forming a second electrolyte layer on the first electrolyte layer, The third step includes a step of forming a layer containing a material represented by the following formula (1) on the dielectric layer, A method for manufacturing a solid electrolytic capacitor. 【Chemistry 2】 In the above formula (1), M represents a valve metal atom. R 1+ represents at least one cationic functional group selected from the group consisting of imidazolium derivatives, pyrrolidinium derivatives, piperidinium derivatives, pyridinium derivatives, morpholinium derivatives, ammonium derivatives, phosphonium derivatives, and sulfonium derivatives, and may have a carbon chain having 1 to 20 carbon atoms between the cationic functional group and the Si molecule, and the carbon chain may have an ester bond, an ether bond, an amide bond, an imide bond, a carbon-carbon unsaturated bond, a carbon ring, or a heterocycle between the chains. In the above formula (1), R 2 represents a hydrogen atom, a carbon chain having 1 to 4 carbon atoms, a valve metal atom, or a polymer in which units of formula (1) are condensed and polymerized together and linked by --Si--O--Si--. In the above formula (1), X - are chlorine, bromine, iodine, acetic acid, decanoic acid, sulfuric acid, lactic acid, nitric acid, benzoic acid, hydroxide, methylsulfuric acid, methanesulfonic acid, ethanesulfonic acid, octanesulfonic acid, allylsulfonic acid, 1,1,2,2-tetrafluoroethanesulfonic acid, nonafluorobutanesulfonic acid, trifluoromethanesulfonic acid, p-toluenesulfonic acid, aminoacetic acid, trifluoroacetic acid, 2-hydroxy-2-phenylacetic acid, 2-aminopropanoic acid, thiosalicylic acid, thiocyanic acid, dicyanamide, dimethyl It represents at least one anion selected from phosphonic acid, diethylphosphonic acid, dibutylphosphonic acid, bis(2,4,4-trimethylpentyl)phosphonic acid, hexafluorophosphoric acid, tetrafluoroboric acid, hexafluoroantimonic acid, tetrachloroaluminic acid, tetrachloroferrate(III), tris(trifluoromethylsulfonyl)methane, bis(fluorosulfonyl)imide, bis(trifluoromethylsulfonyl)imide, and bis(pentafluoroethylsulfonyl)imide.
7. The third step is to react an alkoxy group OR of an ionic liquid represented by the following formula (2): 3 to obtain a compound represented by the following formula (3) having a silanol group, and then OH groups bonded to the surface of the dielectric layer and the silanol groups of the following formula (3) are dehydrated and condensed to fix the material represented by the above formula (1) to the surface of the dielectric layer. 【Chemistry 3】 In the above formula (2), R 3 represents a carbon chain having 1 to 4 carbon atoms.
8. The third step comprises: a step B of hydrolyzing an alkoxyl group of the amino-silane coupling agent to form an amino-silane coupling agent having a silanol group, and then dehydrating and condensing the OH group bonded to the surface of the dielectric layer with the silanol group of the amino-silane coupling agent to fix the amino-silane coupling agent on the surface of the dielectric layer; After the step B, a salt is formed between the amino-based silane coupling agent and phosphoric acid, and an anion X - and exchange the ions with the amino group and the anion X. - and step C, which is bonded by electrical interaction with the compound represented by formula (1) to form a material represented by formula (1), The method for producing the solid electrolytic capacitor according to claim 6 .
9. The third step comprises: a step D of hydrolyzing an alkoxyl group of at least one silane coupling agent selected from an amino-based silane coupling agent, an epoxy-based silane coupling agent, and a thiol-based silane coupling agent to obtain a silane coupling agent having a silanol group, and then dehydrating and condensing the OH group bonded to the surface of the dielectric layer with the silanol group of the silane coupling agent to fix the silane coupling agent on the surface of the dielectric layer; and a step E, which is performed after the step D, of bringing an ionic liquid having an epoxy group represented by the following formula (4) into contact with the silane coupling agent formed on the surface of the dielectric layer in the step D, and then heating the silane coupling agent to bond the epoxy group of the following formula (4) with an amino group, an epoxy group, or a thiol group of the silane coupling agent, thereby forming a material represented by the above formula (1). The method for producing the solid electrolytic capacitor according to claim 6 . 【Chemistry 4】
10. 7. The method for manufacturing a solid electrolytic capacitor according to claim 6, wherein the fourth step includes a step of forming a conductive polymer on the first electrolyte layer by chemical polymerization, or by using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer.
11. a fifth step of forming a third electrolyte layer on the second electrolyte layer; the fifth step includes a step of forming the third electrolyte layer containing a conductive polymer on the second electrolyte layer by using a method selected from a method using a method different from the method used in the fourth step, among chemical polymerization, electrolytic polymerization, or a method using a dispersion liquid containing a conductive polymer or a liquid containing a conductive polymer; The method for producing the solid electrolytic capacitor according to claim 10 .
Citation Information
Patent Citations
Manufacture of solid electrolytic capacitor
JP1994069082A